Does university attendance impact students' political tolerance and open-mindedness: the atypical case of Israel?. (13th April 2021) - Dadon-Golan, Zehorit; Ziderman, Adrian; BenDavid-Hadar, Iris
Abstract : Purpose: A major justification for the state subsidy of university education at public institutions (and, in some countries, of private universities too) is the economic and social benefits accruing to society as whole from a significantly university-educated workforce and citizenship. Based upon a broad range of research findings, a particular societal benefit emanating from higher education relates to good citizenship: that it leads to more open mindedness and tolerant political attitudes. We examined these issues using a representative sample of students from Israeli universities to clarify the extent to which these outcomes would be paralleled in the Israeli setting, where the university experience differs markedly from that found typically in the West. Design/methodology/approach: The research is based on a comparison of political tolerance levels between first- and final-year students enrolled in regular undergraduate study programs (of four days a week or more). However since a change in tolerance is likely to be contingent also on the amount of time that the student spends on campus during the study year, we introduce, as a control group, students enrolled in compressed study programs (of three days a week or less) and compare changes in their tolerance levels with tolerance changes of students enrolled in regular programs. Research questionnaires were distributed to undergraduate students at three universities from the three major districts in Israel–north, south and center. The achieved sample size was 329 students. Findings: Using Difference-in-Differences techniques, we looked for any changes in students' general political tolerance, over the course of their studies. Surprisingly, we found no such effect on political tolerance attitudes. Israeli students are older and often married and though nominally full-time students, they often hold down a full-time job. Thus they come and go to attend lectures but do not otherwise spend much time on campus. Given the somewhat perfunctory nature of the university experience for most Israeli students, it does not to lead to more open-minded and tolerant political attitudes. Practical implications: Some broader, practical applications of the research, beyond the Israeli case, are presented, particularly related to distance learning and to the impact of COVID-19. Attention is given to more recent "Cancel culture" developments on university campuses. Originality/value: The results have wider implications, to other university setting in other countries. Changes in political attitudes may occur in university settings where campus life is well developed, with opportunities for student interaction, formally in extra-curricular events or through social mixing outside the lecture hall. Where the university experience is more minimally confined to attendance at lectures these desirable outcomes may not be forth coming. These findings are relevant to other university frameworks where campus attendance is marginal, such as in open university education and, even more explicitly, in purely internet-based higher education study.